Breeding Site Preferences and Resistance Status of Aedes aegypti in Malang City - Moh Mirza Nuryady; Elly Purwanti; Tutut Indria Permana; Kiky Martha Ariesaka (Jurnal Kesehatan Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant health challenge in urban and semi-urban regions, including Malang City, Indonesia, where Aedes aegypti is the primary vector. This study aimed to identify the breeding site preferences of Ae. aegypti and assess its resistance to 0.8% malathion and 0.05% cypermethrin insecticides. Using a descriptive observational design, ovitraps were deployed in three districts to collect mosquito larvae and eggs, and interviews with residents provided additional data on breeding site preferences. Resistance tests followed WHO guidelines, with mortality rates analysed after insecticide exposure. Results indicated that Ae. aegypti larvae were predominantly found in bathroom water tanks (45%) and flower vases (35%). Resistance status revealed geographical variability: Ae. aegypti in District 1 were resistant to cypermethrin, while populations in Districts 2 and 3 were susceptible, with average status of Ae. Aegypti to cypermethrin is tolerant. For malathion, resistance was widespread, particularly in District 3, with average status of Ae. Aegypti to malathion is resistant. These findings suggest that the use of malathion for vector control in Malang is no longer effective, while cypermethrin remains viable under strict monitoring to prevent future resistance. This study underscores the need for targeted insecticide use and regular monitoring to optimize vector control strategies and minimize DHF transmission.